Studies on the Implied Effectiveness of Online Learning Systems in IAIN Ponorogo - Sofwan Hadi (Journal of Quality Assurance in Islamic Education (JQAIE), 2021)
Complete online learning is mandatory due to COVID 19 that hit Indonesia. In the implementation of fully online learning, there are obstacles and obstacles. So it is necessary to research the conditions of learning while entirely online. This study describes the learning process and obstacles during complete online learning. This study also discusses online learning facilities that are of interest to students. This research uses a descriptive qualitative method to analyze the problem. Respondents in this study were 2047 students. This study resulted in 3 things that happened to fully online learning related to quotas, learning media, and learning facilities. These three components need attention so that full online lectures can run smoothly.